Sarcoidosis: vaginal wall and vulvar involvement - Xu, F.; Cheng, Y.; Diao, et al., R. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2012)
Sarcoidosis is a non-caseous granulomatous disease which could involve numerous organs including lungs, eyes, skin, nervous system, heart, liver.However, the genitourinary tract involvement was rarely reported in sarcoidosis.We report the case of a 45-year-old married woman who presented with 2 months history of a vulval mass as large as a soybean, and did not reveal any remarkable pulmonary signs. Biopsy results showed non-caseous granulomatous inflammation consistent with sarcoidosis in the vulvar lesion. To our knowledge, this is the first reported case of this entity in the world. Based on the related literature, we highlight the possibility of gynecologic involvement in sarcoidosis.